2014
DOI: 10.1097/cin.0000000000000029
|View full text |Cite
|
Sign up to set email alerts
|

Using the Clinical Information System Implementation Evaluation Scale as a Clinical Implementation Strategy

Abstract: The American Nurses Association mandates nursing informaticists to evaluate clinical system implementation processes. When implementing electronic documentation systems, the use of an evaluation tool aids in the identification of end-user concerns and recommendations, which leads to process improvement. At two community hospitals in South Florida, a Clinical Information System Implementation Evaluation Scale was used to evaluate nursing perceptions during the implementation of a new pediatric electronic docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…These findings are consistent with previous findings reported by Brown et al who examined levels of anxiety around computer use among interns and found that gender and computer skill were uncorrelated with satisfaction levels [9]. The lack of correlation between computer experience and satisfaction with EHR is a similar finding to that reported by [13][14][15]. The lack of correlation between these variables could be due to the provision of sufficient training and support, which have been found to mitigate difficulties that could be experienced by nurses and physicians with no previous experience with technology [8,16].…”
Section: Main Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous findings reported by Brown et al who examined levels of anxiety around computer use among interns and found that gender and computer skill were uncorrelated with satisfaction levels [9]. The lack of correlation between computer experience and satisfaction with EHR is a similar finding to that reported by [13][14][15]. The lack of correlation between these variables could be due to the provision of sufficient training and support, which have been found to mitigate difficulties that could be experienced by nurses and physicians with no previous experience with technology [8,16].…”
Section: Main Findingssupporting
confidence: 92%
“…The study adopted the validated and reliable Clinical Information System Implementation Evaluation Scale (CISIES) questionnaire, which was developed by an expert panel based on a highly validated questionnaire [ 12 ] and tested to ensure its validity and enhance its content for evaluating users' satisfaction with EMR. The survey underwent rigorous testing and validation processes, demonstrating a high internal consistency of 0.94 Cronbach’s alpha, thus enhancing its reliability for assessing perceptions of EMR users [ 12 , 13 ] (see Appendix). The purpose of the questionnaire is to solicit clinicians’ perceptions of EHR [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although previous literature was considered during the questionnaire design, to improve the questionnaire’s validity, the majority of questions were taken from a preexisting questionnaire, “ The Clinical Information System Implementation Evaluation Scale (CISIES) ” [ 51 ] The CISIES has been widely used in the field of ICT implementation in health care and has been implemented in various similar studies [e.g. 52 ]. CISIES can gather users’ attitudes on health information systems.…”
Section: Methodsmentioning
confidence: 99%